Effects of selenoprotein extracts from Cardamine hupingshanensis on growth, selenium metabolism, antioxidant capacity, immunity and intestinal health in largemouth bass Micropterus salmoides - Zhang, Hao; Zhao, Long; Zhang, Penghui; Xie, Yuanyuan; Yao, Xinfeng; Pan, Xuewen; Fu, Yifan; Wei, Jiao; Bai, Hongfeng; Shao, Xianping; Ye, Jinyun; Wu, Chenglong (Frontiers in Immunology, 2024)
This study aimed to assess the impact of dietary selenoprotein extracts from Cardamine hupingshanensis (SePCH) on the growth, hematological parameters, selenium metabolism, immune responses, antioxidant capacities, inflammatory reactions and intestinal barrier functions in juvenile largemouth bass (Micropterus salmoides). The base diet was supplemented with four different concentrations of SePCH: 0.00, 0.30, 0.60 and 1.20 g/Kg (actual selenium contents: 0.37, 0.59, 0.84 and 1.30 mg/kg). These concentrations were used to formulate four isonitrogenous and isoenergetic diets for juvenile largemouth bass during a 60-day culture period. Adequate dietary SePCH (0.60 and 1.20 g/Kg) significantly increased weight gain and daily growth rate compared to the control groups (0.00 g/Kg). Furthermore, 0.60 and 1.20 g/Kg SePCH significantly enhanced amounts of white blood cells, red blood cells, platelets, lymphocytes and monocytes, and levels of hemoglobin, mean corpuscular volume and mean corpuscular hemoglobin in the hemocytes. In addition, 0.60 and 1.20 g/Kg SePCH increased the mRNA expression levels of selenocysteine lyase, selenophosphate synthase 1, 15 kDa selenoprotein, selenoprotein T2, selenoprotein H, selenoprotein P and selenoprotein K in the fish liver and intestine compared to the controls. Adequate SePCH not only significantly elevated the activities of antioxidant enzymes (Total superoxide dismutase, catalase, glutathione reductase, glutathione peroxidase), the levels of total antioxidant capacity and glutathione, while increased mRNA transcription levels of NF-E2-related factor 2, Cu/Zn-superoxide dismutase, catalase, glutathione reductase and glutathione peroxidase. However, adequate SePCH significantly decreased levels of malondialdehyde and H2O2 and the mRNA expression levels of kelch-like ECHassociated protein 1a and kelch-like ECH-associated protein 1b in the fish liver and intestine